Health hazard and occupational safety challenges for Unorganized sector workers in India - Mukhtar, Md.Shams; Gotmare, Dr. Preeti R. (The journal of contemporary issues in business and government, 2021)
The unorganized sector plays essential role in Indian economy in terms of employment generation and national domestic product. This sector carries 93 % of the total workforce, in which 79 % are poor and vulnerable section who work and live in contaminated condition and are affected with various chronic diseases. The affordability and accessibility of health services must be ensured for people as “Health is a Human Right”. Medical treatment is now beyond the reach of poor people who are working in the unorganized sector because of increasing costs. Health services are a big problematic issue for India, where a huge number of the population is living in the rural area below the line of poverty (BPL). The people and the Government of India have begun seeking various options for health financing to manage the arising problem of the cost of health care and changing the epidemiological pattern of disease. The research paper shows the issues of health care expenditure and related health problems of unorganized sector workers as well as the extent of utilizing schemes of health insurance are the integral aspects of the proposed research work.